2017
DOI: 10.1002/1878-0261.12060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of somatic copy number alterations on the glioblastoma miRNome: miR‐4484 is a genomically deleted tumour suppressor

Abstract: Glioblastoma (GBM) is the most frequent and most malignant primary brain tumour in adults. GBMs have a unique landscape of somatic copy number alterations (SCNAs), with the concomitant appearance of numerous driver amplifications and deletions. Here, we examined the genomic regions harbouring SCNAs and their impact on the GBM miRNome. We found that 40% of SCNA events covering 70–88% of the genomically altered regions, as identified by GISTIC and RAE algorithms, carried miRNA genes. Of 1426 annotated mature miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…Although studies have investigated the relationship between miRNAs and SCNAs, most were focused on specific miRNAs, SCNAs of specific genes, or a single cancer type [9,10,11,12,13,14,15,16]. The genome-wide association between miRNA expression and SCNAs across several cancer types has not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have investigated the relationship between miRNAs and SCNAs, most were focused on specific miRNAs, SCNAs of specific genes, or a single cancer type [9,10,11,12,13,14,15,16]. The genome-wide association between miRNA expression and SCNAs across several cancer types has not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Maybe these miRNAs do not be expressed in the mitochondria of spermatozoa, or their expression is very low. The miR‐4484 has been showed a putative marker in lymphoma (Tamaddon, Geramizadeh, Karimi, Mowla, & Abroun, ), glioblastoma (Nawaz et al, ), cervical squamous cell carcinoma (Chen et al, ) and breast cancer (Tamaddon et al, ) and in occupational noise‐induced hearing loss (Li et al, ). Previous studies showed the role of miR‐4463 overexpression in inhibiting aberrant vascular smooth muscle cell (VSMC) migration(Wang et al, ), enhancing H 2 O 2 induced oxidative stress and apoptosis (Wang, He, Deng, He, & Zhou, ), novel biomarker in arteriosclerosis obliterans (He et al, ) and polycystic ovary syndrome (Ding et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is located at chromosome 10q26.2, and it contains 83 bases. Up to now, the expression of miR-4484 has been evaluated in several types of cancer, such as breast cancer 15 , glioblastoma 16 , diffuse large B-cell lymphoma 17 , as well as oral lichen planus 18 . Interestingly, there is only one study, by Christmann et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although MMP-21 is not predicted to be a target of miR-4484 by bioinformatics programs described above, it has attracted our attention since miR-4484, and MMP-21 genes are located in the immediate vicinity on chromosome 10, and MMP-21 has not been evaluated in SSc yet. miR-4484 is an intragenic miRNA that resides in the first intron of the uroporphyrinogen III synthetase (UROS) gene and MMP-21 resides downstream to UROS (at the distance of ~13 kb) 16 . Based on this data, it is tempting to speculate whether there exists any inter-relationship between the expression of miR-4484 and MMP-21 16 .…”
Section: Discussionmentioning
confidence: 99%